RANSOMWARE: MECHANISM OF ACTION AND METHODS OF PROTECTION - Luchyk , S. D.; Zaika , I. V.; Saienko, S. L. (Systems and Technologies, 2026)
Among the many contemporary digital threats, malicious software in the ransomware category occupies a dominant and distinctive position, posing an unprecedented danger not only to data confidentiality but also to human safety and the resilience of entire sectors of the economy, including critical infrastructure and the public sector. Global digitalization, the transition to cloud technologies, and the expansion of corporate network boundaries have significantly increased the attack surface. The impact of ransomware on organizations, as it continues to evolve and become more sophisticated, results in enormous financial losses, paralysis of business processes, and reputational damage. This necessitates a fundamental reassessment of approaches to information security and gives this topic considerable social and scientific significance. The aim of this article is to provide a comprehensive examination of the ransomware phenomenon – from typological classification and historical development to a detailed study of the technical mechanisms of attack execution and the development of comprehensive practical recommendations for protection. The article identifies and outlines the historical stages in the emergence and spread of ransomware: from basic encryptors to modern “Ransomware-as-a-Service” (RaaS) business models, which have substantially lowered the barrier to entry for cybercriminals. The study examines the algorithm of a modern ransomware attack, with a detailed description of its key phases: initial compromise (through phishing, exploitation of RDP vulnerabilities, or zero-day vulnerabilities), lateral movement, exfiltration, and encryption. Based on the analysis conducted, an effective ransomware protection system is proposed, grounded in the Zero Trust concept and combining technological, organizational, and procedural components. Organizations need to implement rigorous patch management to ensure the immediate updating of vulnerable services, mandatorily use multi-factor authentication (MFA) for all entry points, and regularly conduct practical phishing simulations for personnel. Technical protection should include strict network segmentation and be based on the mandatory deployment of EDR/XDR-class solutions capable of automatically blocking anomalous activities before irreversible consequences occur. It is critically important to implement end-to-end cryptographic encryption of confidential data at rest, which will render such data useless to hackers in the event of a leak, as well as to strictly adhere to the “3-2-1” backup rule with isolated copies. Every institution should develop, formally approve, and regularly test an Incident Response Plan, while establishing in advance a communication channel with governmental protection agencies such as CERT-UA.